PRELIMINARY REPORT OF THREE COMPONENTS OF GEOMAGNETIC FIELD MEASURED ON BOARD THE ICEBREAKER SHIRASE DURING JARE-30, 1988-1989 - ノギ, ヨシフミ; セアマ, ノブカズ; イセザキ, ノブヒロ; NOGI, Yoshifumi; SEAMA, Nobukazu; ISEZAKI, Nobuhiro (National Institute of Polar Research, 1990)
P(論文) Measurement of three components of geomagnetic field was carried out on board the icebreaker SHIRASE during the 30th Japanese Antarctic Research Expedition (JARE-30). Vector anomalies of geomagnetic field were obtained and the directions of magnetic lineations were determined from the vector anomalies. They are in good agreement with the results previously reported along the ship's tracks (e. g. ROYER et al. : Tectonophysics, 155,235,1988; ROYER and SANDWELL : J. Geophys. Res., 94,13755,1989), except for the Antarctic continental margin and the Enderby Basin. In the Antarctic continental margin, N-S trending magnetic structure that coincides with the Australian-Antarctic depression is detected between Australia and Antarctica and the local magnetic anomaly that seems to be caused by the Napier Complex appears between 50°E and 60°E along 63°S. Further, in the Enderby Basin around 60°S, N-S and NNE-SSW trending magnetic lineations which have never been reported before are detected. These results may suggest new constraints on the evolution of the Indian Ocean. departmental bulletin paper